2015
DOI: 10.3892/ol.2015.3478
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin suppresses migration and invasion of human endometrial carcinoma cells

Abstract: Abstract. Curcumin, a widely used Chinese herbal medicine, has historically been used in anti-cancer therapies. However, the anti-metastatic effect and molecular mechanism of curcumin in endometrial carcinoma (EC) are still poorly understood. The purpose of this study was to detect the anti-metastatic effects of curcumin and the associated mechanism(s) in EC. Based on assays carried out in EC cell lines, it was observed that curcumin inhibited EC cell migration and invasion in vitro. Furthermore, following tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 23 publications
3
41
0
1
Order By: Relevance
“…Based on regression fit analysis, the concentrations of LC that Once the concentrations went below these levels, the suppression of proliferation was slight. This result agrees with that of Chen et al [2], who demonstrated the inhibitory effect of LC on proliferation in EC cells. Thus, a concentration range of LC higher or lower than this was selected for the subsequent experiments.…”
Section: Proliferation Inhibition Of Lc On Ec Cell Linessupporting
confidence: 83%
See 3 more Smart Citations
“…Based on regression fit analysis, the concentrations of LC that Once the concentrations went below these levels, the suppression of proliferation was slight. This result agrees with that of Chen et al [2], who demonstrated the inhibitory effect of LC on proliferation in EC cells. Thus, a concentration range of LC higher or lower than this was selected for the subsequent experiments.…”
Section: Proliferation Inhibition Of Lc On Ec Cell Linessupporting
confidence: 83%
“…On this basis, we selected Ishikawa (high ER expression) and HEC-1 (low ER expression) EC cell lines as target cells and investigated the inhibitory effects of LC on proliferation [2]., in that LC significantly inhibited the proliferation of both Ishikawa and HEC-1 cells, which indicated that LC completely retained the bioactive inhibitory effects of curcumin on cell proliferation in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6B,C, triticumoside significantly inhibited MMP2/9 expression in a dosedependent manner, suggesting that triticumoside modulates the expression of MMPs to inhibit cancer cell metastasis. In order to confirm these results, we utilized curcumin as MMP2/9 inhibitor [13] and performed gene expression analysis after triticumoside treatment following preincubation with curcumin. Results indicated that pretreatment with curcumin strongly inhibits MMP2/9 expression in triticumoside-treated cells (Fig.…”
Section: Triticumoside Inhibits Migration Of Nsclc A549 Cells Throughmentioning
confidence: 99%